Urinary angiotensin-converting enzyme 2 and its activity in cats with chronic kidney disease - Kuo, Tzu-Chien; Hsu, Wei-Li; Wu, Vin-Cent; Jan, Tong-Rong; Tsai, Pei-Shiue Jason; Lee, Ya-Jane (Frontiers in Veterinary Science, 2024)
Introduction Angiotensin-converting enzyme 2 (ACE2) played an important role in the renin-angiotensin-aldosterone system (RAAS) and it was proved to be renoprotective in renal disease. Urinary angiotensin-converting enzyme 2 (uACE2) has been shown to reflect renal injury in human and experimental studies, but its role in feline kidney disease remains unknown. Aims Our objectives involve comparing uACE2 concentrations and activities in cats across CKD stages with healthy controls, investigating the relationship between uACE2 concentrations, activities, and clinicopathological data in feline CKD patients, and assessing the predictive abilities of both for CKD progression. Methods A retrospective, case–control study. The concentration and activity of uACE2 were measured by commercial ELISA and fluorometric assay kits, respectively. The concentration was adjusted to give uACE2 concentration-to-creatinine ratios (UACCRs). Results In total, 67 cats consisting of 24 control and 43 chronic kidney disease (CKD), including 24 early-stage CKD and 19 late-stage CKD, were enrolled in this study. UACCR values were significantly higher in both early-stage (2.100 [1.142–4.242] x 10−6) and late-stage feline CKD (4.343 [2.992–5.0.71] x 10−6) compared to healthy controls (0.894 [0.610–1.076] x 10−6; p < 0.001), and there was also significant difference between-early stage group and late-stage group (p = 0.026). Urinary ACE2 activity (UAA) was significantly lower in CKD cats (1.338 [0.644–2.755] x pmol/min/ml) compared to the healthy cats (7.989 [3.711–15.903] x pmol/min/ml; p < 0.001). UACCR demonstrated an independent, positive correlation with BUN (p < 0.001), and UAA exhibited an independent, negative correlation with plasma creatinine (p < 0.001). Both UACCR and UAA did not yield significant results in predicting CKD progression based on the ROC curve analysis. Conclusion and clinical importance uACE2 concentration and activity exhibit varying changes as renal function declines, particularly in advanced CKD cats.